2014
DOI: 10.1007/s00709-014-0746-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic studies based on rDNA ITS, cpDNA trnL intron sequence and cladode characteristics in nine Protasparagus taxa

Abstract: The genus Asparagus comprises three subgenera of cladode bearing plants: Protasparagus, Asparagus, and Myrsiphyllum. The interspecific delimitation of the subgenus Protasparagus is ill-defined till date. In the present study, interspecific phylogenetic relationships among nine taxa of Protasparagus based on ribosomal DNA internal transcribed spacer region (ITS1-5.8S-ITS2) sequence and the chloroplast DNA trnL intron sequence conservation with their cladode morphology, anatomy, and stomatal characteristics have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…More than 60 species distributed in the world have been mentioned under this subgenus in the publication of Kanno & Yokoyama (). After Obermeyer & Immelman (), who categorized this subgenus into diverse morphological series based on vegetative and floral characters, recently we have demonstrated for the first time the molecular phylogenetic status of this subgenus in particular (Saha et al, ). Saha et al () reported the monophyletic nature of the subgenus Protasparagus and have drawn an explicit interspecific relationship among nine taxa of this subgenus based on the primary sequence data of rDNA ITS, cpDNA trnL intron and cladode characteristics and ultimately grouped them into four strongly supported distinct subclades (I, II, III and IV).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…More than 60 species distributed in the world have been mentioned under this subgenus in the publication of Kanno & Yokoyama (). After Obermeyer & Immelman (), who categorized this subgenus into diverse morphological series based on vegetative and floral characters, recently we have demonstrated for the first time the molecular phylogenetic status of this subgenus in particular (Saha et al, ). Saha et al () reported the monophyletic nature of the subgenus Protasparagus and have drawn an explicit interspecific relationship among nine taxa of this subgenus based on the primary sequence data of rDNA ITS, cpDNA trnL intron and cladode characteristics and ultimately grouped them into four strongly supported distinct subclades (I, II, III and IV).…”
mentioning
confidence: 98%
“…Protasparagus , one of the three subgenera of the genus Asparagus , is characterized by diverse forms of cladodes (modified photosynthetic stem with a single leaf like internode) which ranges from linear flattened to acicular shapes (Saha et al, ). More than 60 species distributed in the world have been mentioned under this subgenus in the publication of Kanno & Yokoyama ().…”
mentioning
confidence: 99%
“…In addition, The trnL group I intron and the intergenic spacer between trnL and trnF are widely used in plant systematics [9]. On the other hand, only a few molecular studies on the genus Asparagus was reported to have been carried out based on cpDNA and the rDNA ITS region [10].…”
mentioning
confidence: 99%
“…Generally, reactive oxygen species have various detrimental effects on the cell, like damage of DNA, oxidations of poly-desaturated fatty acids in lipids, oxidations of amino acids in proteins, and oxidatively inactivate specific enzymes by oxidation of co-factors [12][13]. Antioxidants are thought to protect cells against specific diseases by prohibiting the harmful effects of the free radical-mediated process [10][11][12][13][14].…”
mentioning
confidence: 99%
“…All studied regions were selected from chloroplast DNA. The first one was the trnL (UAA) intron, whose sequences have been commonly used for evolutionary studies among related species (Taberlet et al, 1991;Gielly et al, 1996;Zhang et al, 2004;Chen et al, 2005;Dizkirici et al, 2013;Saha et al, 2014). The second region, the trnL (UAA) -F (GAA) intergenic spacer (IGS), was selected due to its utility at the generic and infrageneric level as a former region (Taberlet et al, 1991;Gielly and Taberlet, 1994;Bakker et al, 1999;Kores et al, 2001;Hoggard et al, 2004).…”
Section: Introductionmentioning
confidence: 99%